Face Maintenance Rituals and Communication Strategies Used in Puja Astawa’s YouTube Videos - Novita Mulyana; Yana Qomariana (Fakultas Bahasa dan Budaya Asing (FBBA), Universitas Muhammadiyah Semarang, 2023)
YouTube, a video sharing platform, is famously used these days, not only due to its function as part of entertainment, but also a media of interaction. Unlike, face-to-face interaction or other computer-mediated interaction, YouTube served multi-party interaction and three levels of communication. Its uniqueness leads to questions on whether people engaged in this interaction manage maintaining their interlocutor’s face and what communication strategies are used amid this multi-party interaction considering it may involve people from different social and cultural background. This qualitative research was aimed to analyse the first level communication in YouTube videos by using interactional sociolinguistics approach in order to figure out the types of face maintenance rituals as well as the communication strategies used by the participants in YouTube videos. The data source of the study was Puja Astawa’s YouTube videos, one of the most popular content creators in Bali. In collecting the data, documentation method and note taking technique were used. The data were further analysed using the face maintenance theory proposed by Goffman and communication strategies proposed by Canale and Swain. The result of the analysis shows that presentational rituals is the main rituals used by the participants in Puja Astawa’s YouTube videos. In terms of communication strategies, there are three strategies found, namely (1) code switching, (2) repetition, (3) the use of Balinese particles. Code switching is the mostly used strategy while the use of Balinese particles is the least used strategy.